Study Of Fingerprint Patterns And Their Relationship With Blood Groups And Gender In Erode, Tamilnadu (Journal of Pharmaceutical Negative Results, 2023)
Background and Objectives: Fingerprint is one of the most mature biometric technologies and is considered as legitimate proofs of evidence in court of law. Blood grouping can also be utilized in genetic research, forensic pathology and anthropology. In this study an effort is made to study the relationship between fingerprint patterns with ABO, Rh blood groups and gender. Methods: 100 male and 100 female subjects from students and teaching staffs of Government Erode Medical college Perundurai were included after excluding any congenital or acquired deformities of fingers. Fingerprints of subjects are obtained with help of pre-inked strips and blood grouping done by slide method. Results: In study A, B and O blood groups were equally distributed with 31.5% each and AB was least common blood group (5.5%). Majority of subjects were Rh +ve (92.5%). A group (37.2%) was most common among males and O group (37.4%) in females. Loops was most frequently observed (53%) followed by whorls (26.4%), composites (14.35%) and arches (6.25%) in whole study group and in both genders. Loop and arch pattern of fingerprints was most common in B group, whorls in O, composites in A blood group. Loops were most consistent in little fingers, whorls in ring fingers, arches in index fingers and composites in thumb of both hands. In sub-patterns ulnar loop pattern (95.2%) out-numbered radial loop. Concentric whorls (77.5%) were most common type of whorls. Among arches, tented arches (56.8%) and among composites, central pocket loops (53.1%) were most predominantly seen. conclusion: The regression equations derived were found to be statistically significant and correlate the relationships between the fingerprint patterns and blood groups and also fingerprint patterns and gender.